2022
DOI: 10.1002/cbf.3698
|View full text |Cite
|
Sign up to set email alerts
|

Possible effects of fibroblast growth factor 21 on vascular calcification via suppressing activating transcription factor 4 mediated apoptosis and osteogenic transformation in rats

Abstract: Vascular calcification (VC), a significant risk factor of many cardio‐cerebral vascular diseases, is a perplexing issue with no effective treatment in clinical work up to now. Endoplasmic reticulum stress (ERS) mediated apoptosis has been proved to be a significant mechanism for initiating VC process. Activating transcription factor 4 (ATF4), a key transcription factor of ERS, is most closely associated with VC. Fibroblast growth factor 21 (FGF21), an atypical member of the FGFs family, has a protective biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Regarding ERN1, research indicates that ERN1 mRNA is the actual target of hcmv-miR-UL148D and its encoded protein IRE1α is translationally repressed by the overexpression of hcmv-miR-UL148D resulting in the attenuation of apoptosis [ 72 ]. Regarding ATF4, research has demonstrated that activated transcription factor 4 (ATF4) plays a pivotal role as the key transcription factor in ERS [ 73 ], and is at least partially implicated in ERS-mediated apoptosis [ 74 ]. Although the studies [ 73 , 74 ] focus on vascular calcification rather than osteoarthritis, they underscore the critical role of ATF4 in modulating endoplasmic reticulum stress and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding ERN1, research indicates that ERN1 mRNA is the actual target of hcmv-miR-UL148D and its encoded protein IRE1α is translationally repressed by the overexpression of hcmv-miR-UL148D resulting in the attenuation of apoptosis [ 72 ]. Regarding ATF4, research has demonstrated that activated transcription factor 4 (ATF4) plays a pivotal role as the key transcription factor in ERS [ 73 ], and is at least partially implicated in ERS-mediated apoptosis [ 74 ]. Although the studies [ 73 , 74 ] focus on vascular calcification rather than osteoarthritis, they underscore the critical role of ATF4 in modulating endoplasmic reticulum stress and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ATF4, research has demonstrated that activated transcription factor 4 (ATF4) plays a pivotal role as the key transcription factor in ERS [ 73 ], and is at least partially implicated in ERS-mediated apoptosis [ 74 ]. Although the studies [ 73 , 74 ] focus on vascular calcification rather than osteoarthritis, they underscore the critical role of ATF4 in modulating endoplasmic reticulum stress and apoptosis. Concerning Bid, the study indicates that the concurrent elevation of Bim, Bid and Bad, along with reduced levels of Bcl-2 and Bcl-xl may render cells more susceptible to apoptosis during sepsis.…”
Section: Discussionmentioning
confidence: 99%